A study on the adoption intention of cold chain prepared Dishes based on consumer orientation mentality - Luo, Feng; Shang , Wei; Gan , Junwei (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background:  Cold chain prepared dishes, as a new type of food with low temperature and dual attributes, have attracted more and more attention from consumers. From the perspective of consumers' brand positioning mentality, this study integrated the brand, quality and other attributes of cold chain prepared vegetables, and studied the positioning mentality and adoption behavior of Chinese consumers   In this study, three cold-chain prefabricated dishes, "pickled cabbage fish", "tomato Braised beef brisket" and "Huangpi fishball", were selected as investigation objects. Contribution:  The contribution of this study is that different food value attributes explain the law of consumers' willingness to adopt cold chain prepared dishes through brand positioning mentality, and find out how different degrees of vulnerability and quality warranty Method:  Based on ZMET survey method, product effect data were used to analyze and verify structural equation model. Results:  Different value evaluation directly affects consumers' brand positioning mentality, brand positioning mind as an intermediate variable has a significant correlation with adoption intention. The degree of vulnerability moderates the relationship between value evaluation and brand positioning mentality, and the degree of warranty period regulates the relationship between quality value, brand positioning mentality and adoption intention respectively. Conclusion:  It also provides new marketing tools and theories for entrepreneurs and marketers in the cold chain food industry, which contributes to the promotion and diffusion of cold chain prepared food for consumers